Membangun Budaya Literasi Baca Tulis Berbasis Iman Kepada Kitab Al -Qur’an Menuju Era Revolusi 5.0 - Nilal Muna Fatmawati; Wahid Hakim Azzaky; Salwa Azizah; Shodiq Abdullah (STIKes Ibnu Sina Ajibarang, 2025)
Advances in technology and information are a challenge in facing conditions in the 5.0 revolution era. This requires a person to be able to have skills in building a literacy culture. The Qur'an is a spark so that a person can be armed with faith in utilizing technology. Literacy rooted in Qur'anic values can be a strong moral and spiritual foundation in shaping the character of a superior and globally competitive society. This study aims to analyze the importance of building a culture of literacy based on the Qur'an and the challenges and solutions in facing the industrial revolution 5.0 era. This research method uses library research. Data collection is done by reviewing theories from various scientific articles, books, and reading sources relevant to the research topic. The results of this study discuss the importance of a faith-based approach to the Qur'an as a source of inspiration and motivating a literacy culture to form individuals competent in science, civilized and globally competitive. In facing challenges in the era of revolution 5.0, the Qur'an can be a solution in guiding people to utilize technology with literacy skills based on faith and morality. In addition, building a culture of literacy in the era of revolution 5.0 can also form a critical, ethical and responsible attitude.